2014
DOI: 10.1002/jps.24073
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Enhancement and Formulation of Rapid-Release Lornoxicam Mini-Tablets

Abstract: The aim was to enhance the dissolution of lornoxicam and to produce mini-tablets with an optimised system to provide a rapid release multiparticulate formulation. Lornoxicam systems were prepared through co-evaporation with either PEG or Pluronic® F-68 and adsorption onto Neusilin® US2 alone or co-adsorption in the presence of different amounts of polysorbate 80. All systems were characterised by FT-IR, DSC, XRD, flowability and dissolution techniques. Mini-tablets were prepared using the system with the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…This observation was due to the conversion of GLC from crystalline to amorphous state. Similar behavior was also recorded from other researchers [13,20,45].…”
Section: Dsc Studysupporting
confidence: 86%
See 3 more Smart Citations
“…This observation was due to the conversion of GLC from crystalline to amorphous state. Similar behavior was also recorded from other researchers [13,20,45].…”
Section: Dsc Studysupporting
confidence: 86%
“…Tween 80 and Pluronics were chosen as non-ionic surfactants known to enhance the solubility and dissolution of many water insoluble drugs as reported previously [13,20,22,23].…”
Section: Effect Of Surfactant Addition On the Adsorption Of Glc Onto mentioning
confidence: 99%
See 2 more Smart Citations
“…The drug contained in the mini-tablets gets released at different rates, depending upon composition of mini tablets. Based on the release kinetic parameters calculated, it can be concluded that minitablets containing HPMC K100M are particularly suitable to release the drug over hours of time periods 9 .…”
Section: Release Profilementioning
confidence: 99%